Strategi Membangun Keunggulan di Era Disrupsi: Kajian di Pondok Pesantren Annur Azzubaidi, Konawe, Sulawesi Tenggara - Nur Alim; Syahrul Syahrul (Al-Izzah: Jurnal Hasil-Hasil Penelitian, 2021)
This article describes the struggle of the Pesantren Annur Azzubaidi in building excellence in the era of disruption. The aspects studied are: developing the vision of the Pesantren, large-scale planning, strengthening the skills of students, and strengthening community relations. The deepening process is carried out through qualitative research with the narrative method, where the data is obtained through observation, interviews and document studies. Meanwhile, data analysis goes through the stages: data collection, data reduction, data display, and data verification. The results showed that: 1) the development of the vision of the Pesantren Annur Azzubaidi leads to the development of quality human resources in science; 2) large-scale planning embodied in short-term plans, medium-term plans, and long-term plans; 3) train students' skills in various fields such as agriculture, animal husbandry, arts, and entrepreneurship; 4) build partnerships and strengthen relationships with the community. This study recommends the need for further research on the resilience of the cottage tradition in the industrial era 4.0.